Evaluation of corrosion and scaling tendency indices in water distribution system: a case study of Torbat Heydariye, Iran. Issue 54 (19th November 2016) - Mirzabeygi, Majid; Naji, Mozhgan; Yousefi, Nader; Shams, Mahmoud; Biglari, Hamed; Mahvi, Amir Hossein
Abstract: Corrosion and scaling tendency of water is an etiology of economic and health concerns in the water supply systems. The aim of this study was to investigate the water stability in Torbat Heydariye drinking water distribution system. This cross-sectional study was done with cluster sampling schemes and 90 samples were collected by simple random sampling from 15 clusters. All samples were taken from water distribution network during 2014. Also, the water stability was determined using Langelier saturation index (LSI), Ryznar Stability index (RSI), Puckorius scaling index (PSI), Larson-Skold index (LS), and Aggressiveness index (AI). Physical and chemical analysis showed that the mean of pH, total dissolve solid, electrical conductivity, chloride concentration, sulfate, temperature, bicarbonate, total alkalinity, calcium hardness were 7.75, 896 mg/L, 1, 254 μMoh/cm, 203 mg/L, 201 mg/L, 22.7°C, 251 mg/L, 209 mg/L as CaCO3, 111.6 mg/L as CaCO3, respectively. The results illustrated that the average values of LSI, RSI, PSI, LS, and AI was 0.02 (±0.125), 7.71 (±0.2), 12.04 (±0.125), 7.55 (±0.3), and 1.7 (±0.456), respectively. Moreover, According to LSI, RSI, PSI, LS, and AI, corrosion tendency in the water network was 40, 100, 93.3, 94, and 33.3%, respectively. The severity of corrosion in different regions of Torbat Heydariye was displayed using Geographic Information System.